(untitled) (Biological Sciences - PJSIR, 1995)
Fieldexperiments wereconductedduringamanseasonof 1990withtworicevarietiesnamely,Nizersail andIR20, todeterminetheinfluencesofpestsonriceyieldandinterrelationshipamongtheattackingpests.Abundanceofricepests showed negativecorrelations with riceyield.Path coefficient analysisrevealsthat abundanceofScirpophaga incertu- Las and Sesamia inferens (ricestemborers) hadthemaximumnegativedirecteffectonriceyield.Step-wiseregression equations showed the highest relative importance of rice stem borers for their damaging capabilities on rice yield followed by Dicladispa armigera (rice hispa).